2015
DOI: 10.1007/s00726-015-1976-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations of circulating asymmetric dimethylarginine and cell adhesion molecules with metformin use in patients with type 2 diabetes mellitus and stable coronary artery disease

Abstract: Metformin, the drug of first choice in type 2 diabetes mellitus (T2DM), reduces cardiovascular (CV) morbidity and mortality in part independently of improved glycemic control and changes in traditional risk factors. However, there are discordant reports on the effects of metformin on endothelial function in T2DM. Our aim was to compare biochemical endothelial markers in patients with stable coronary artery disease (CAD) and T2DM stratified by metformin use. We studied 70 patients (29 women, age 68 ± 9 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
0
15
0
1
Order By: Relevance
“…Whether the beneficial effects of the combined treatment seen in this are due to an improvement of the L-Arg/NO pathway and are mediated by l-arginine, metformin or both remains to be investigated. It is worth mentioning that metformin administration (1655 mg/d) may enhance ADMA synthesis, but decrease plasma-soluble vascular cell adhesion molecule-1 (sVCAM-1) in patients suffering from type 2 diabetes mellitus and stable coronary artery disease (Kruszelnicka et al 2015).…”
Section: Effect Of Steroid and Creatine Medicationmentioning
confidence: 99%
“…Whether the beneficial effects of the combined treatment seen in this are due to an improvement of the L-Arg/NO pathway and are mediated by l-arginine, metformin or both remains to be investigated. It is worth mentioning that metformin administration (1655 mg/d) may enhance ADMA synthesis, but decrease plasma-soluble vascular cell adhesion molecule-1 (sVCAM-1) in patients suffering from type 2 diabetes mellitus and stable coronary artery disease (Kruszelnicka et al 2015).…”
Section: Effect Of Steroid and Creatine Medicationmentioning
confidence: 99%
“…VCAM-1 is an inflammatory protein that is up-regulated in preeclampsia and associated with endothelial dysfunction. 61 Metformin previously has been shown to reduce endothelial cell inflammatory gene and protein expression 83,84 and serum VCAM-1 concentrations in patients with diabetes mellitus 59 and impaired glucose tolerance. 60 We demonstrated that, in the presence of TNFa that is an inflammatory cytokine that is up-regulated in preeclampsia, 76 metformin reduced VCAM-1 expression in endothelial cells.…”
Section: Metformin Rescues Endothelial Dysfunction and Impaired Vasodmentioning
confidence: 99%
“…Metformin has been reported to have vasoprotective properties; epidemiologic studies have shown that it reduces cardiovascular morbidity in patients with polycystic ovarian syndrome 26 and diabetes mellitus. 57,58 This has been attributed to its ability to reduce vascular cell adhesion molecule 1 (VCAM-1), 59,60 which is a molecule that is expressed on the luminal surface of blood vessels in the presence of inflammation and is increased in preeclampsia. 61 Metformin has also been reported to induce vasodilation of diabetic rat vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ADMA levels were similar among patients with no difference in their glycemic control receiving either metformin either repaglinide [257]. Worth noting, a study among patients with diabetes mellitus type 2 and stable coronary artery disease revealed that patients receiving metformin have higher circulating ADMA levels as compared to subjects not receiving metformin [258]. Therefore, it remains obscure whether metformin actually exerts part of its beneficial action via regulation of ADMA.…”
Section: Blood Glucose Lowering Medicationsmentioning
confidence: 98%